Kepastian Hukum dan Perlindungan Hak Atas Tanah: Analisis terhadap PP Nomor 48 Tahun 2025 - Ivana Aprilia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study analyzes legal certainty and the protection of land rights in the regulation of abandoned land under Government Regulation Number 48 of 2025. It focuses on two main issues: whether the regulation fulfills the principles of legal certainty and clarity of norms, and whether the mechanism for determining abandoned land ensures adequate legal protection for landowners. This research uses a normative juridical method with statutory and conceptual approaches. The results show that although the regulation aims to optimize land utilization and prevent land abandonment, several provisions remain ambiguous and open to multiple interpretations, thereby weakening legal certainty. In addition, the mechanism for determining abandoned land has not fully guaranteed legal protection, particularly in terms of procedural fairness, transparency, and the right to be heard. This condition creates an imbalance between state authority and individual land rights. Therefore, improvements are necessary to strengthen normative clarity and ensure a proportional balance between public interest and private rights